Impact of Favoritism/ Nepotism on Emotional Exhaustion and Education Sabotage: The Moderating Role of Gender - Shneikat, Belal; Abubakar, Mohammed Abubakar; İlkan, Mustafa (Harvard Academic Forum, 2016)
Favoritism/nepotism are common practice at most organizations. This study attempts to provide an insight by measuring the impact of favoritism/nepotism on emotional exhaustion and education sabotage. Data was collected from teaching/research assistants at six universities in North Cyprus. The interplay among the study variables was observed via SEMs. Implications and consequences of organizational politics like favoritism/nepotism and work-related strain like emotional exhaustion are discussed.
Keywords: favoritism/nepotism, emotional exhaustion, education sabotage